Mechanical behavior of temperature-sensitive gels under equilibrium and transient swelling. (July 2018) - Drozdov, A.D.
Abstract: Water uptake by a thermo-responsive gel is strongly affected by temperature: the gel swells below its volume phase transition temperature T c and shrinks above T c . Observations reveal two types of equilibrium swelling diagrams: discontinuous (with degree of swelling Q falling abruptly at T c ) and continuous (with Q decreasing smoothly with temperature). A constitutive model is developed for the mechanical behavior of a temperature-sensitive gel subjected to swelling that accounts for changes in its structure (phase separation) at T c . Adjustable parameters are found by fitting experimental data in equilibrium swelling tests, transient deswelling–reswelling tests, and tensile-compressive tests on poly( N, N -diethylacrylamide) gel with a continuous equilibrium swelling curve and poly( N − n -propylacrylamide) gel with a discontinuous diagram. Numerical simulation demonstrates qualitatively different responses of gels with discontinuous and continuous swelling diagrams.